GESTAÇÃO NO PRESÍDIO: MODOS DE SUBJETIVAÇÃO NA PRIVAÇÃO DE LIBERDADE - Halanna Silva de Miranda (2023)
This study aims to understand processes of subjectivation of pregnant women deprived of liberty. This is a qualitative research using a semi-structured interview to collect information, with open questions about the gestational state and the experience of giving birth in prison. The research subjects are pregnant women detained in the women's penitentiary complex of the Francisco de Oliveira Conde prison located in the city of Rio Branco, capital of the State of Acre. The analysis of the collected data was carried out based on Foucauldian references with emphasis on the understanding of discipline, panopticon, control of bodies, conception of crime, punitive measures and the status of the criminal as a transgressor of the social pact. The results of this research made it possible to recognize that, just as institutions model behaviors through the discursive bias of knowledge-power, motherhood also does so, differing, however, by the attributed social characteristic whose main focus is to manage women's bodies strengthened by great disciplines such as Obstetrics, which stipulates correct ways of mothering in family planning, in prenatal care, during childbirth and in the postpartum period. Thus, the socially agreed control mechanisms for motherhood intervene in the management of what it means to be a mother. Nevertheless, pregnant women prisoners are included in this double power game, the prison institution and the maternity hospital, which, in turn, can be punitive in the same way as the prison, producing different modes of subjectivation and objectivity to which they are subjected.